Implementasi Aplikasi Pembelajaran Dasar Pada SLB B (Tunarungu Dan Wicara) Dengan Menggunakan Macromedia Flash - Dian Rustamaji, Sri Siswanti (Jurnal Ilmiah SINUS, 2013)
This learning application system is to get closer to the students on the subject matter and enhance students' understanding and clearly and can assist teachers in presenting the material to the students about learning SLB B (hearing and speech impaired).Data collection methods include interviews, observations, and literature. This study included interviews with the method to the field of learning in Extraordinary School class of B Mitra Amanda Trayu Boyolali and material about the learning that is taught to students. Observations made with the observation, recording and retrieving data involving teachers how about learning groove. While the literature carried out to obtain the relevant reference in making learning applicationsThe results of the implementation of learning applications with Macromedia Flash using the questionnaire method is by distributing questionnaires containing questions about the respondents. Questionnaire given to the teachers and students with hearing impairment and speech. The results for the teachers themselves learning applications is very helpful in presenting the material to students. Respond students with learning applications students can receive lessons well and easy to understand. Overall learning applications is feasible for children with hearing impairment and speech base class (class 1 and 2)Key words :learning application, Macromedia Flash, hearing and speech impaired